Multi-Agent-Based Simulation XII International Workshop, MABS 2011, Taipei, Taiwan, May 2-6, 2011, Revised Selected Papers - Villatoro, Daniel; Sabater-Mir, Jordi; Sichman, Jaime Simao; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 12th International Workshop on Multi-Agent-Based Simulation, MABS 2011, held in Taipei, Taiwan, in May 2011. The 10 revised selected and extended papers presented were carefully reviewed and selected from 21 submissions. The topics covered are MABS in scientometrics; MABS in politics, transit and policy; pedestrian, crowds and large scale MABS; and MABS modeling.
Keywords: Artificial intelligence; Software engineering; Computers; Algorithms; Computer simulation; Special purpose computers; Artificial Intelligence; Software Engineering; Computation by Abstract Devices; Algorithm Analysis and Problem Complexity; Simulation and Modeling; Special Purpose and Application-Based Systems